The effect education a childbirth preparation pocketbooks on the level anxiety of pregnant women in the third trimester - Indriyani, Mei Indriyani; Aryani, Farida; Zuliyati, Isti Chana (Alma Ata University Press, 2024)
Background: Among the 373,000 pregnant women in Indonesia, 107,000 (28.7%) experience anxiety as they approach childbirth. On Java Island, approximately 35,387 (52.3%) pregnant women in their third trimester report similar anxiety. Lack of knowledge is one of the causing factors that lead a person to experience anxiety. Efforts to reduce maternal anxiety levels can be made through health education. Providing health education supported by media, such as pocketbooks, can help increase maternal awareness and thereby reduce mothers' antenatal anxiety levels as they prepare for childbirth. Objectives: This study aims to figure out the effect of education using a childbirth preparation pocketbook on the level of antenatal anxiety of mothers in the third trimester of pregnancy at Public Health Centers in Bantul Regency.Methods: The current research was quasi-experimental research carried out using pretest-posttest control group design. The study population consisted of third-trimester pregnant women attending ANC visits. There were 54 respondents in the experimental group and 54 respondents in the control group involved as samples, consisting of those from Kasihan I, Banguntapan I, and Piyungan Public Health Centers. This research employed Quota Sampling as the sampling technique and utilized a respondent characteristic data questionnaire along with the HARS (Hamilton Anxiety Rating Scale) questionnaire as the research instrument. Results: The results of the Mann-Whitney test showed a p-value of 0.011 (p < 0.05), indicating that education using a pocketbook significantly affects antenatal anxiety levels in third-trimester pregnant women. The pre-test and post-test values for each group also demonstrated significant differences. . Conclusions: Education using pocketbooks has an effect on reducing antenatal anxiety in pregnant women preparing for labor.